Investigating the Domestic Layers Adaptation During Pandemic - Karimah, Afifah; Paramita, Kristanti Dewi (Interiority, 2020)
This paper expands the theoretical understanding of building layers proposed by Brand (1995) by investigating changes in the domestic environment during the COVID-19 pandemic. Brand’s layer framework breaks a built environment into “shearing layers” to examine its adaptation processes. This paper argues that ways of managing the risk of virus transmission in the built environment redefine the understanding of these layers. This paper takes the perspective of interiority to address these layers as instruments with the spatial qualities required of a resilient domestic environment. The study unpacks the theory of Brand’s layer framework, proposing the principles by which layers adapt to protect the domestic environment during the COVID-19 pandemic. It then offers readings on the occurrence of change in the domestic environment in which such adaptation principles are performed. Such occurrences consist of intensifying layer changes to assist intense uses, merge between layers to assist movements, the construction of new layer forms, and reconfiguration of multiple layers for a prolonged change. Apart from redefining the very understanding of layers, this paper addresses how spatial change is not driven only by physical deterioration, but also by the performative creation of scenarios to protect the domestic environment during the pandemic.